2021
DOI: 10.7759/cureus.17654
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Venous Clinical Severity Score With Dermatology Life Quality Index Among Patients With Chronic Venous Insufficiency: A Cross-Sectional Study

Abstract: IntroductionChronic venous insufficiency (CVI) is characterized by inadequate functioning of venous valves in the lower limb. CVI is associated with a significant reduction in patient's quality of life (QOL). The severity of CVI was determined by CEAP (clinical, etiological, anatomical, pathophysiological) classification and venous clinical severity score (VCSS). The study is aimed to evaluate and correlate Dermatology Life Quality Index (DLQI) with VCSS, CEAP in patients with CVI. MethodsA cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Patients in C1 and C6 classes were not included in our study in order to provide a similar patient population. While Gürdal Karakelle et al 30 reported that the mean VCSS score of patients whom 66.7% were in C6, was 16.08 ± 6.98; Poulose et al 31 found that the mean values of patients whom 49.2% were in C4, was 11.67. In outcome measures of our study, although 52.5% of the participants were in C3 class, the clinical severity score was found to be higher than Poulose et al This difference may be due to the inhomogeneity of the CEAP classification of the patients participating in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in C1 and C6 classes were not included in our study in order to provide a similar patient population. While Gürdal Karakelle et al 30 reported that the mean VCSS score of patients whom 66.7% were in C6, was 16.08 ± 6.98; Poulose et al 31 found that the mean values of patients whom 49.2% were in C4, was 11.67. In outcome measures of our study, although 52.5% of the participants were in C3 class, the clinical severity score was found to be higher than Poulose et al This difference may be due to the inhomogeneity of the CEAP classification of the patients participating in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of life for patients with CVI is impacted by their symptoms, treatment options, and frequent medical appointments. Beyond the fact that CVI can cause lower extremity pain, swelling, skin changes, and lead to infection and ulcer development, there is superimposed anxiety, depression, low self-esteem, and social deprivation [ 91 , 92 ]. The progression to venous leg ulcers, as discussed subsequently, amplifies psychosocial effects in relation to ulcer odors and excessive exudate that triggers further feelings of low self-esteem with social isolation and depression [ 93 ], and in older patients, further worsens quality of life [ 24 ].…”
Section: Reviewmentioning
confidence: 99%